2014
DOI: 10.1007/s11999-013-3395-7
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Hip Osteoarthritis Have a Phenotype With High Bone Mass and Low Lean Body Mass

Abstract: Background Although hip osteoarthritis (OA) is common, its etiology is poorly understood. Specifically, it is not known whether hip OA is associated with abnormal relationships among the anthropometric and musculoskeletal characteristics that are associated with OA in general. Questions We asked whether patients with primary hip OA have a phenotype with higher bone mineral density (BMD), higher BMI, larger skeletal size, lower lean body mass, and higher fat content. Material and Methods We included 30 women an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 31 publications
(51 reference statements)
3
21
0
1
Order By: Relevance
“…One cross‐sectional study showed that both the fat mass (OR = 1.69, 95% CI: 1.07‐2.66 for men per SD; OR = 1.67, 95% CI: 1.07‐2.62 for women per SD) and fat mass percentage (OR = 1.87, 95% CI: 1.09‐3.21 for men per SD; OR = 1.87, 95% CI: 1.11‐3.15 for women per SD) were positively associated with hip OA . One cohort study reported that fat mass could increase the risk of developing hip OA (RR = 1.29, 95% CI: 1.18‐1.41).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…One cross‐sectional study showed that both the fat mass (OR = 1.69, 95% CI: 1.07‐2.66 for men per SD; OR = 1.67, 95% CI: 1.07‐2.62 for women per SD) and fat mass percentage (OR = 1.87, 95% CI: 1.09‐3.21 for men per SD; OR = 1.87, 95% CI: 1.11‐3.15 for women per SD) were positively associated with hip OA . One cohort study reported that fat mass could increase the risk of developing hip OA (RR = 1.29, 95% CI: 1.18‐1.41).…”
Section: Resultsmentioning
confidence: 93%
“…Then, full articles were extracted for further assessment after reviewing the titles and abstracts. Eventually, 19 studies (10 cross‐sectional, 5 case‐control and 4 cohort studies) were included in the present systematic review and meta‐analysis. The study screening process is shown in Figure , and the study characteristics and NOS score of the 19 included articles are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Again, this study can only show an association between knee OA and the studied variables, does not imply causation, and should therefore be regarded as hypothesis-generating. Studies suggest that OA and osteoporosis are distinct different diseases [9] and an association between OA in the hip, knee, ankle, and feet and a high BMD has also been found [3,4,6,8,13,17,20,23]. It has been speculated that a high BMD may result in a denser and stiffer skeleton with less load absorptive ability, a phenotype that may be involved in the pathogenesis of primary OA [25].…”
Section: Resultsmentioning
confidence: 99%
“…Primary OA leads to local effects on the skeleton, including cysts, subchondral sclerosis, and osteophytes [12]; however, OA is also associated with high bone mineral density (BMD) [3,8,11,17,26,27], high BMI [15,26], and small bone size [8]. It is unclear whether this phenotype is found in all patients with OA, irrespective of the affected joint.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation